Photonic nanostructures for advanced light trapping in thin crystalline silicon solar cells. Issue 1 (25th June 2014) - Trompoukis, Christos; Abdo, Islam; Cariou, Romain; Cosme, Ismael; Chen, Wanghua; Deparis, Olivier; Dmitriev, Alexandre; Drouard, Emmanuel; Foldyna, Martin; Caurel, Enric Garcia‐; Gordon, Ivan; Heidari, Babak; et al.
<x xml:space="preserve">Abstract</x> We report on the fabrication, integration, and simulation, both optical and optoelectrical, of two‐dimensional photonic nanostructures for advanced light trapping in thin crystalline silicon (c‐Si) solar cells. The photonic nanostructures are fabricated by the combination of various lithography (nanoimprint, laser interference, and hole mask colloidal) and etching (dry plasma and wet chemical) techniques. The nanopatterning possibilities thus range from periodic to random corrugations and from inverted nanopyramids to high aspect ratio profiles. Optically, the nanopatterning results in better performance than the standard pyramid texturing, showing a more robust behavior with respect to light incidence angle. Electrically, wet etching results in higher minority carrier lifetimes compared to dry etching. From the integration of the photonic nanostructures into a micron‐thin c‐Si solar cell certain factors limiting the efficiencies are identified. More precisely: (a) the parasitic absorption is limiting the short circuit current, (b) the conformality of thin‐film coatings on the nanopatterned surface is limiting the fill factor, and (c) the material damage from dry etching is limiting the open circuit voltage. From optical simulations, the optimal pattern parameters are identified. From optoelectrical simulations, cell design considerations are discussed, suggesting to position the junction on the opposite side of the nanopattern.<inline-graphic xlink:href="ark:/27927/pgh3730r78w" content-type="pssa201431180-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />